An improved model for prediction of the cone-jet formation in electrospray with the effect of space charge. (January 2020) - Jiang, Zhengwei; Gan, Yunhua; Shi, Yanling
Abstract: The presence of space charge can cause a non-negligible effect in some electrospray applications, which, however, was ignored in previous numerical studies. In the present study, the formation of the cone-jet in the electrospray process is investigated with considering the space charge effects. The governing equations of fluid flow and electrostatics are coupled in the numerical method. The charge transport equation is implemented with no simplification and the volume of fraction (VOF) method is employed to track the liquid-gas interface. An improved model of considering the effect of charged droplet emitted from the tip of cone-jet on the external electric field is proposed. By considering the space charge effects, the improved model can achieve better accuracy in predicting the shape of the cone-jet by reducing the mean relative error from 12.5% to 4.2%. The flow field in the cone-jet is obtained and the vortices are found to play an important role in the cone-jet formation. In terms of the current produced by the cone-jet, the prediction error is reduced from 19 %-39% to 10 %-16% by considering the space charge. Further validation is conducted by comparing the simulated results with the prediction of the scaling laws. It was found that the prediction of the improved model fits better with the scaling laws based on both the analytical and experimental results. The new model can provide more reliable and detailed information for the simulation of other processes in the electrospray, i.e., the jet breakup and droplets motion. Highlights: Space charge is considered in modeling the cone-jet formation during electrospray. The improved model predicts the cone-jet shape more accurately. The space charge affects the flow field and vortices inside the liquid cone. The predicted current during cone-jet formation fits better with the scaling laws.